2022
DOI: 10.3389/fmicb.2022.867392
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Early-Branching Wolbachia Reveals Functional Enrichment on Horizontally Transferred Genes

Abstract: Wolbachia is a widespread endosymbiont of insects and filarial nematodes that profoundly influences host biology. Wolbachia has also been reported in rhizosphere hosts, where its diversity and function remain poorly characterized. The discovery that plant-parasitic nematodes (PPNs) host Wolbachia strains with unknown roles is of interest evolutionarily, ecologically, and for agriculture as a potential target for developing new biological controls. The goal of this study was to screen communities for PPN endosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 118 publications
2
10
0
Order By: Relevance
“…So, we speculate that extensive gene fractionation occurred during the evolutionary history of arthropod-infecting Wolbachia strain genomes, which promoted the retention of genes that are essential for survival and host adaptation. In contrast, nematode-infecting Wolbachia strains have established long-lasting mutualistic relationships with their specific hosts (Darby et al, 2012;Godel et al, 2012), leading to a stable state of the genome that may lead to the loss of large numbers of genes (Gerth et al, 2014) or to form species-specific novel genes (Weyandt et al, 2022), as recently reported in another Wolbachia study.…”
Section: Discussionmentioning
confidence: 94%
“…So, we speculate that extensive gene fractionation occurred during the evolutionary history of arthropod-infecting Wolbachia strain genomes, which promoted the retention of genes that are essential for survival and host adaptation. In contrast, nematode-infecting Wolbachia strains have established long-lasting mutualistic relationships with their specific hosts (Darby et al, 2012;Godel et al, 2012), leading to a stable state of the genome that may lead to the loss of large numbers of genes (Gerth et al, 2014) or to form species-specific novel genes (Weyandt et al, 2022), as recently reported in another Wolbachia study.…”
Section: Discussionmentioning
confidence: 94%
“…The contigs obtained from the sequencing of the six Wolbachia -positive samples were highly similar between themselves. Thus, to increase the coverage of the assembly, the authors decided to pool the 192 contigs and named the final assembly w Tex [ 23 ]. Regarding the hosts of w Tex, two genera might be associated this pool: Helicotylenchus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, an outgroup should be selected from outside the studied phylum, but the other Rickettsiales are too phylogenetically distant. Inferring Wolbachia phylogenies with Anaplasma and Ehrlichia might generate long-branch attraction artefacts and multiple polytomies [3,5,8,10,23,32,33,35,36,48,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. This is why more than half of the produced topologies of Wolbachia do not use an outgroup (electronic supplementary material, table S4).…”
Section: The Use Of An Outgroup With Wolbachia: No Perfect Solution I...mentioning
confidence: 99%
See 2 more Smart Citations